2003
DOI: 10.1079/joh2002142
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of intestinal parasitoses in relation to environmental and sociocultural parameters in La Plata, Argentina

Abstract: Environmental parameters influencing the distribution of parasite species in three neighbourhoods of differing socioeconomic conditions in La Plata, Argentina were analysed. Coproparasitological screenings were performed in children up to 14 years old from a marginal zone (100), a suburban neighbourhood (101), and an urban area (91) in 1999--2000. The presence of parasite species in environmental samples (water and soil) and the degree of association among parasite communities was documented and evaluated. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
27
0
29

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 6 publications
5
27
0
29
Order By: Relevance
“…At the same time, each individual was performed a blood smear to evaluate eosinophiles in peripheral blood, and a serial coproparasitologic study, processed by modified Telemann technique (Gamboa et al 2003).…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, each individual was performed a blood smear to evaluate eosinophiles in peripheral blood, and a serial coproparasitologic study, processed by modified Telemann technique (Gamboa et al 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Studies carried out in different countries report different percentages. In South America, lower prevalence was observed in Brazil by LUDWIG et al 9 and in Argentina by GAMBOA et al 7 . Prevalence higher than those found in this study were informed in Brazil 14 and Chile 16 .…”
mentioning
confidence: 93%
“…In developing countries, the presence, incidence and prevalence of intestinal parasitic infections in different regions are indicators of the health status of the population 7 . The results obtained in this study revealed about 45% of parasited individuals, with the protozoa/ helminths ratio being different in both areas and clear predominance of the protozoa.…”
mentioning
confidence: 99%
“…The prevalence of intestinal parasitic infections is one of the most accurate indicators of socioeconomic conditions of a population (3) and may be associated with several determinant factors, such as adequate sanitation, fecal pollution of water and foods, sociocultural factors, contact with animals, lack of basic sanitation, as well as host age and type of infecting parasite (4) .…”
Section: Introductionmentioning
confidence: 99%